1990
DOI: 10.1136/adc.65.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus infection in cystic fibrosis.

Abstract: Twenty seven patients with cystic fibrosis under the age of 12 years and 27 matched patients with asthma were followed up in a prospective study for one year. The isolation rate of non-capsulated strains ofHaemophilus influenzae from cough swabs and sputum specimens taken at routine clinic visits every two months was significantly greater in cystic fibrosis than in asthma. Haemophilus parainfluenzae was equally common in both groups. During exacerbations the isolation rate of H influenzae in cystic fibrosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
(17 reference statements)
0
34
0
Order By: Relevance
“…We found that H. influenzae was associated with lower FVC. While H. influenzae has been found to be associated with pulmonary exacerbations [32], and with higher leukocyte and neutrophil counts in bronchoalveolar lavage fluid from CF infants [5]; to our knowledge, the association of H. influenzae with lung function has previously only been evaluated in one study using FEV1 among children aged .6 yrs [33] and a significant effect was not detected in that study. However, the clinical significance of an effect of H. influenzae on vital capacity without an effect on airway obstruction (forced expiratory flows) is unclear.…”
mentioning
confidence: 60%
“…We found that H. influenzae was associated with lower FVC. While H. influenzae has been found to be associated with pulmonary exacerbations [32], and with higher leukocyte and neutrophil counts in bronchoalveolar lavage fluid from CF infants [5]; to our knowledge, the association of H. influenzae with lung function has previously only been evaluated in one study using FEV1 among children aged .6 yrs [33] and a significant effect was not detected in that study. However, the clinical significance of an effect of H. influenzae on vital capacity without an effect on airway obstruction (forced expiratory flows) is unclear.…”
mentioning
confidence: 60%
“…In addition, BRUMBACK et al [42] found that recent H. influenzae infection was associated with lower forced vital capacity in preschool children with CF. Infection with H. influenzae has also been associated with pulmonary inflammation [14,31] and pulmonary exacerbations [43] in children with CF. These data indicate that H. influenzae is highly pathogenic in young children with CF, and should be targeted for eradication and treatment to improve lung function outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 82% of children with P. aeruginosa had previous isolates of S. aureus or H. influenzae (14). During exacerbations of CF lung disease in children, the isolation rate of H. influenzae was significantly greater than at other times (38).…”
Section: Nthi In Early Cf Lung Diseasementioning
confidence: 99%
“…For reasons that are not fully understood, NTHi causes persistent infections despite appropriate antibiotic therapy in diseases with abnormalities of mucociliary clearance, such as COPD (35,41) and CF (11,(38)(39)(40). Because H. influenzae forms biofilms on airway epithelia that display decreased susceptibility to antimicrobials, this may help to explain why such infections persist despite antibiotic treatment in OM, COPD, and CF (40,42,43).…”
Section: Nthi Biofilms: a Possible Link To Early Cf Lung Diseasementioning
confidence: 99%